Magnetic Resonance Imaging in the Pre-Surgical Staging of Breast Cancer: Our Experience. (2nd January 2017) - Rabasco, Paola; Caivano, Rocchina; Dinardo, Giuseppina; Gioioso, Matilde; Lotumolo, Antonella; Iannelli, Giancarlo; Villonio, Antonio; La Torre, Giuseppe; D'Errico, Stefano; Macarini, Luca; Guglielmi, Giuseppe; Cammarota, Aldo
ABSTRACT: Purpose : To investigate the clinical impact of magnetic resonance imaging (MRI) in the detection of multifocal–multicentric breast cancers, already identified by mammography and ultrasound, and analyzed histologically, to evaluate its role in preoperative staging. Materials and methods : From January 2012 to February 2014, 188 patients, aged 28 to 74 years, newly diagnosed with breast cancer on conventional imaging (mammography and ultrasound) were enrolled. They underwent preoperative contrast-enhanced 3T MRI. Patients underwent surgery according to international guidelines. Results of all diagnostic procedures were compared. Results : Among the 188 patients, 163 (87%) had a unilateral and unifocal tumor at both conventional imaging; MRI diagnosed 22/22 (100%) of multifocal and multicentric tumors, the combination of mammography and ultrasound diagnosed 12/22 (54%), and mammography alone diagnosed 8/22 (36%) multifocal and multicentric tumors. MRI prompted a change in surgical strategy in 10/188 (5%) patients. This change comprised mastectomy instead of conservative surgery ( n = 7) and more extensive conservative surgery ( n = 3). Conclusions : MRI was confirmed to show higher sensitivity than conventional imaging in detecting multifocal and multicentric breast cancers.